Memory and metamemory in obsessive-compulsive disorder - TOPÇUOĞLU, VOLKAN (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Studies on the link between checking and memory problems have produced equivocal results regarding a general memory deficit in patients with obsessive-compulsive disorder and subclinical checkers. However, there is clear and consistent evidence that patients with obsessive-compulsive disorder (OCD) show lack of confidence in their memory performance. The purpose of the present study was to investigate memory and metamemory performance (feeling-of-knowing judgments) for neutral and threat-related material in three groups: OCD patients (OCs), subclinical checkers (SCs), and normal controls (NCs). Participants studied a list of neutral and threat word pairs. After an initial cued-recall test, they provided feeling-of-knowing (FOK) judgments for unrecalled word pairs, followed by a recognition test. The results showed that OCs but not SCs were impaired in both recall and recognition compared to NCs. OCs were also less confident about their future memory performance than the other two groups, as reflected in their lower FOK ratings. Moreover, FOK judgments of the OCs were not reliable predictors of their recognition performance. Finally, neither OCs nor SCs showed any evidence of memory bias for threat-relevant information. The results support the idea of a general memory and a metamemory deficit in OCs. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: obsessive-compulsive disorder; memory; metamemory; feeling-of-knowing; CONFIDENCE; CHECKERS; SCALE; BIAS; INVENTORY; DEFICITS